Potential‐based achievement goals. (26th June 2014) - Elliot, Andrew; Murayama, Kou; Kobeisy, Ahmed; Lichtenfeld, Stephanie; Martin, Andrew
<x xml:space="preserve">Abstract</x> Background Self‐based achievement goals use one's own intrapersonal trajectory as a standard of evaluation, and this intrapersonal trajectory may be grounded in one's past (past‐based goals) or one's future potential (potential‐based goals). Potential‐based goals have been overlooked in the literature to date. Aims The primary aim of the present research was to address this oversight within the context of the 3 × 2 achievement goal framework. Samples The Study 1 sample was 381 US undergraduates; the Study 2 sample was 310 US undergraduates. Methods In Study 1, we developed scales to assess potential‐approach and potential‐avoidance goals and tested their factorial validity with exploratory and confirmatory factor analyses. In Study 2, we used confirmatory factor analysis to test both the separability of past‐based and potential‐based goals and their higher order integration within the self‐based category. Results Study 1 supported the factorial validity of the potential‐approach and potential‐avoidance goal scales. Study 2 supported the separability of past‐based and potential‐based goals, as well as their higher order integration within the self‐based category. Conclusions This research documents the utility of the proposed distinction and paves the way for subsequent work on antecedent and consequences of potential‐approach and potential‐avoidance goals. It highlights the importance of focusing on distinct types of growth‐based goals in the achievement goal literature.